2022
DOI: 10.1038/s41598-022-12076-w
|View full text |Cite
|
Sign up to set email alerts
|

EGFR inhibition reverses resistance to lenvatinib in hepatocellular carcinoma cells

Abstract: Hepatocellular carcinoma (HCC) is a leading cause of cancer-related death worldwide. Lenvatinib is approved as a first-line treatment for unresectable HCC. The therapeutic duration of lenvatinib is limited by resistance, but the underlying mechanism is unclear. To establish lenvatinib-resistant cells, Hep3B cells were initially treated with 3 µM lenvatinib. The concentration was gradually increased by 1 µM or 0.5 µM per week and it reached to 7.5 µM 2 months after the initial exposure to lenvatinib. The biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…S4, E and F), suggesting the necessity to compare the efficacy and underlying mechanisms of different drugs against the same targets. To explore whether the LICOB pharmaco-proteogenomic data are consistent with well-studied drug resistance mechanisms, we investigated lenvatinib response and the epidermal growth factor receptor (EGFR)–related pathways that confer resistance to lenvatinib treatment in HCC ( 26 , 27 ). We found that lenvatinib resistance (high AUC) was positively correlated with high abundance of proteins and negatively correlated with DNA methylation of genes associated with EGFR tyrosine kinase inhibitor resistance (fig.…”
Section: Resultsmentioning
confidence: 99%
“…S4, E and F), suggesting the necessity to compare the efficacy and underlying mechanisms of different drugs against the same targets. To explore whether the LICOB pharmaco-proteogenomic data are consistent with well-studied drug resistance mechanisms, we investigated lenvatinib response and the epidermal growth factor receptor (EGFR)–related pathways that confer resistance to lenvatinib treatment in HCC ( 26 , 27 ). We found that lenvatinib resistance (high AUC) was positively correlated with high abundance of proteins and negatively correlated with DNA methylation of genes associated with EGFR tyrosine kinase inhibitor resistance (fig.…”
Section: Resultsmentioning
confidence: 99%
“…In specific, inhibition of fibroblast growth factor receptor (FGFR) by Lenvatinib treatment leads to feedback activation of the EGFR-PAK2-ERK5 signaling axis. The combination of the EGFR inhibitor Gefitinib or Erlotinib and Lenvatinib displays enhanced anti-proliferative effects ( He et al, 2022 ; Jin et al, 2021 ). HGF/c-MET signaling is closely associated with drug resistance in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…To start, researchers knew that Lenvatinib works to decrease ERK phosphorylation to inactivate the MAPK pathway and prevent cell growth. However, in resistant cell lines, there was an increase in ERK phosphorylation 32 . The cause of this discrepancy was narrowed down to two genes, one of them being EGFR.…”
Section: How Patients Have Been Responding To Lenvatinib (Resistance ...mentioning
confidence: 97%